Moses and the Israelite according to Tarikh al-Tabari - مرمر ناصری پور (تاریخ ادبیات, 2013)
Moses is one of the characters in the Bible, the Qur'an, and historical books, especially Tarikh al- Tabari. He was a great prophet, and according to the traditions of 3 religions, he brought the Israelite out of Egypt. According to the Torah and Quran, as well as Tarikh al-Tabari, Moses' mother put him in a basket and entrusted him to the Nile River, and Pharaoh's wife Asiya took him out of the water. Pharaoh was pleased to take Moses as a son, and Moses grew up in Pharaoh's court. Moses was prosecuted for killing a Coptic and went to Madyan. There he served for eight years with the priest of Madyan, who according to Muslim accounts was called Shu'ayb. Then he married the daughter of Shu'ayb. The Jews and the Christians and the Muslims believed that returning from Madyan, he was chosen as a prophet to the Israelite. This article examines the position of Prophet Moses in Tarikh al-Tabari to clarify his place among the prophets.